New Trend Switching Behavior of Bank Customers - Akhmad Hafandi; Masdar Hilmy; Puji Handayati (Universitas Negeri Malang, 2021)
This study aims to identify the factors that influence switching behavior of customers in selecting Sharia banking services in Indonesia. This study employed a positivistic research paradigm to explain and predict the determinants of switching behavior of banking customers. In this study, a quantitative approach was adopted to examine the relationship between variables, determine variable causality, generalization, and prediction. The results of data analysis indicate that the important factors that determine switching behavior are religiosity, internet banking, and employee hospitality. Additionally, conditions that can hinder switching behavior are the fact that customers are increasingly rational. Lastly, the strategy that need to be developed by Islamic banking related to switching behavior is to maintain customer loyalty. The managerial implication of this research is that efforts are needed to increase understanding of Islamic banking to a higher level of education through a rational approach. Future research is expected to include price variables, number of offices, and other rational-based services to explore in more detail the determinants of switching behavior. Keywords: Switching behavior, Banking customer, Sharia banksJEL Classification: D91; G21; G41